Coexistence of atypical adenoma, adenoma with bizarre nuclei and follicular variant of papillary carcinoma of the thyroid - Teresa Pusiol; Maria Grazia Zorzi; Doriana Morichetti (Wolters Kluwer Medknow Publications, 2013)
Coexistence of atypical adenoma, adenoma with bizarre nuclei and follicular variant of papillary carcinoma is described in the same thyroid, with study of p53 expression. A 72-year-old woman presented to the endocrinology out-patient unit for a routine follow-up visit. Patient underwent a total thyroidectomy. Histological examination revealed a solid nodular neoplasm with the longest diameter of 0.8 cm in the upper pole of the left lobe. The neoplasm showed the histological features of follicular variant of papillary carcinoma with moderate diffuse immunoreactivity for p53. The lower pole of the right lobe showed two adjacent nodules with histological features respectively of atypical adenoma and adenoma with bizarre nuclei, with strong diffuse immunoreactivity for p53.